Substrate-Integrated Defected Ground Structure for Single- and Dual-Band Bandpass Filters With Wide Stopband and Low Radiation Loss - Tang, Deshan; Han, Changxuan; Deng, Zhixian; Qian, Huizhen Jenny; Luo, Xun (IEEE transactions on microwave theory and techniques, 2021)
In this article, two types of substrate-integrated defected ground structure (SIDGS) resonant cells with wide upper stopband and low radiation loss are presented for filter implementation. Such SIDGS resonant cells are composed of two dissimilar DGSs surrounded by the bottom ground and metal-vias, which cannot only introduce wide stopband with low radiation loss but also be flexible for integration. Based on the aforementioned SIDGS resonant cells, single- and dual-band bandpass filters (BPFs) are designed and fabricated. The single-band BPF centered at 2.40 GHz exhibits an ultrawide upper stopband up to 19.7 GHz with a rejection level of 31 dB, whereas the measured stopband total loss (i.e., including radiation, metal, and substrate loss) remains about 30% up to 19.3 GHz. The dual-band BPF operated at 2.10 and 3.78 GHz exhibits an ultrawide upper stopband up to 17.8 GHz with a rejection level of 23 dB, whereas the measured stopband total loss is less than 16% up to 11.4 GHz.